2010
DOI: 10.1051/0004-6361/201014731
|View full text |Cite
|
Sign up to set email alerts
|

Disc-oscillation resonance and neutron star QPOs: 3:2 epicyclic orbital model

Abstract: The high-frequency quasi-periodic oscillations (HF QPOs) that appear in the X-ray fluxes of low-mass X-ray binaries remain an unexplained phenomenon. Among other ideas, it has been suggested that a non-linear resonance between two oscillation modes in an accretion disc orbiting either a black hole or a neutron star plays a role in exciting the observed modulation. Several possible resonances have been discussed. A particular model assumes resonances in which the disc-oscillation modes have the eigenfrequencies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 85 publications
(95 reference statements)
0
15
0
Order By: Relevance
“…As emphasized by Urbanec et al (2010b), , Kluźniak & Rosińska (2013), Török et al (2014), Rosińska et al (2014) and Boshkayev et al (2015), Newtonian effects following from the influence of the quadrupole moment act on the orbital frequencies in a way opposite to that which is related to relativis- tic effects following from the increase of the angular momentum. The behaviour of the relations shown in the left panel of Figure 3 is determined by this interplay.…”
Section: Results For the Rp Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…As emphasized by Urbanec et al (2010b), , Kluźniak & Rosińska (2013), Török et al (2014), Rosińska et al (2014) and Boshkayev et al (2015), Newtonian effects following from the influence of the quadrupole moment act on the orbital frequencies in a way opposite to that which is related to relativis- tic effects following from the increase of the angular momentum. The behaviour of the relations shown in the left panel of Figure 3 is determined by this interplay.…”
Section: Results For the Rp Modelmentioning
confidence: 98%
“…These can be confronted with models of rotating NS based on a modern equation of state (EoS, e.g. Urbanec et al 2010b). In Török et al (2012) we have identified and explored mass-angular-momentum relations implied in Kerr spacetimes by individual QPO models.…”
Section: Aims and Scope Of This Papermentioning
confidence: 99%
“…Abramowicz et al (2003a,b); Kluźniak & Abramowicz (2001) introduced the resonance model with the upper frequency corresponding to the vertical epicyclic frequency and the lower frequency corresponding to the radial epicyclic frequency, which accords with observational data quite well in the black-hole binary systems (Török et al, 2005. But the last two models show the inconsistent with the subsequent twin kHz QPO observations (Belloni et al, 2007;Jonker et al, 2002a;Muno, 2004;Strohmayer & Bildsten, 2006;Urbanec et al, 2010;van der Klis, 2006;Wijnands et al, 2003;Zhang et al, 2006a).…”
Section: Introductionmentioning
confidence: 78%
“…where C depends on the NS structure and equation of state [29][30][31]. For a NS of radius R = 11 km and mass M = 1.5 M , we choose C = 1.1 .…”
Section: Emission From Ns Surfacementioning
confidence: 99%